2004
DOI: 10.1590/s0104-11692004000700008
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de drogas lícitas e ilícitas en escolares y factores de protección y riesgo

Abstract: Duvicq CGF, Pereira NR, Carvalho AMP. Consumo de drogas lícitas e ilícitas en escolares y factores de protección y riesgo. Rev Latino-am Enfermagem 2004 março-abril; 12(número especial):345-51. Los objetivos de la investigación fueron identificar la población consumidora de drogas lícitas e ilícitas entre escolares de sexto año básico de escuelas municipalizadas urbanas de CONSUMPTION OF LICIT AND ILLICIT DRUGS IN STUDENTS AND CONSUMPTION OF LICIT AND ILLICIT DRUGS IN STUDENTS AND CONSUMPTION OF LICIT AND I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Individual confounding factors included: age in years ( Carlini et al, 2010 ; Hibell et al, 2007 ), male or female ( Carlini et al, 2010 ; Hibell et al, 2007 ), maternal schooling ( Malta, Mascarenhas, Porto, Barreto, & Neto, 2014 ), school's administration (public or private) ( Carlini et al, 2010 ), student engaged in a remunerated activity ( Souza & Silveira-Filho, 2007 ), reported having had sexual relations ( Malta et al, 2014 ), live with parents at the time of the interview ( Brooks et al, 2012 ; Horta, Horta, & Pinheiro, 2006 ), students' perception of how parents would react if they come home drunk ( Brooks et al, 2012 ; Larrosa & Palomo, 2010 ), reported having suffered domestic violence in the preceding 30 days ( Larrosa & Palomo, 2010 ), reported having been victim of bullying in the preceding 30 days ( Luk, Wang, & Simons-Morton, 2012 ; Strauch, Pinheiro, Silva, & Horta, 2009 ), reported missing school without parents' permission in the preceding 30 days ( Fraile Duvicq, Pereira, & Carvalho, 2004 ; Malta et al, 2014 ), reported having close friends ( Fazel, Hoagwood, Stephan, & Ford, 2014a ; Fazel, Patel, Thomas, & Tol, 2014b ).…”
Section: Methodsmentioning
confidence: 99%
“…Individual confounding factors included: age in years ( Carlini et al, 2010 ; Hibell et al, 2007 ), male or female ( Carlini et al, 2010 ; Hibell et al, 2007 ), maternal schooling ( Malta, Mascarenhas, Porto, Barreto, & Neto, 2014 ), school's administration (public or private) ( Carlini et al, 2010 ), student engaged in a remunerated activity ( Souza & Silveira-Filho, 2007 ), reported having had sexual relations ( Malta et al, 2014 ), live with parents at the time of the interview ( Brooks et al, 2012 ; Horta, Horta, & Pinheiro, 2006 ), students' perception of how parents would react if they come home drunk ( Brooks et al, 2012 ; Larrosa & Palomo, 2010 ), reported having suffered domestic violence in the preceding 30 days ( Larrosa & Palomo, 2010 ), reported having been victim of bullying in the preceding 30 days ( Luk, Wang, & Simons-Morton, 2012 ; Strauch, Pinheiro, Silva, & Horta, 2009 ), reported missing school without parents' permission in the preceding 30 days ( Fraile Duvicq, Pereira, & Carvalho, 2004 ; Malta et al, 2014 ), reported having close friends ( Fazel, Hoagwood, Stephan, & Ford, 2014a ; Fazel, Patel, Thomas, & Tol, 2014b ).…”
Section: Methodsmentioning
confidence: 99%